Ab Initio Investigation of the Role of CO Adsorption on the Physical Properties of 55-Atom PtCo Nanoalloys - Guedes-Sobrinho, Diego; Freire, Rafael L. H. [UNESP]; Chaves, Anderson S.; Da Silva, Juarez L. F. (Amer Chemical Soc, 2017)
The knowledge of the physical and chemical properties of PtCo nanoparticles as a function of the Pt/Co composition and atomic distribution is crucial for several potential applications, which includes catalysis, anticorrosion, data storage, etc. However, our current atom-level understanding is far from satisfactory, in particular due to the challenges to take into account chemical environment effects. In this work, we report a density functional theory investigation of the structural, energetic, and electronic properties of binary 55-atom PtCo particles at a saturated CO atmosphere (31 molecules), (CO)(31)/Pt(n)Coss(55-n). For PtCo in the gas phase, which adopts an icosahedron-like (ICO-like) structure in the lowest-energy configurations for all studied compositions, we found a rough correlation between stability and the number of bonds among the Pt and Co species; i.e., the stability (excess energy) increases (decreases) by increasing the number of Pt and Co bonds and with a minimum at about n = 28-42 (Pt-rich). However, at a saturated CO atmosphere, we found a stability displacement toward higher Co concentration (n = 6-20, Co-rich), which can be explained by the structural expansion of the nanocluster surface driven by the CO ligands. That is, the CO adsorption contributes to release the strain, which is induced by the attractive Coulomb interactions between the anionic surface and cationic core regions. Furthermore, for particular compositions (n = 42), we found a displacement of the Co atoms toward the surface upon the CO adsorption, which can be explained also by strain release as the adsorption energy of CO is larger on the Pt surfaces, which could favor Pt-rich surfaces.